The Determinant of Furniture Business Performance in Jepara Regency - Swasta, Sri; Wijayanto, Andi; Listyorini, Sari (Cv. Syntax Corporation Indonesia, 2023)
In the current business context, entrepreneurial orientation (EO) has been highlighted as key to improving firm performance. Despite the overall positive evidence on the association between EO and firm performance, scholars have stressed the importance of taking into account and properly managing intermediate capabilities. This study was conducted to examine the effect of entrepreneur orientation on business performance and Innovation. This research was carried out in Jepara Regency. The sample in this study amounted to 75 Furniture Business Owners. The data collection method used a questionnaire. The analytical method used in this study is SEM with Smart PLS 3.3.3. The results of this study indicate that entrepreneur orientation does not have a significant influence on business performance. Innovation can mediate the influence of Entrepreneur Orientation on Business Performance. This study makes a novel contribution to the EO kinds of literature as it finds evidence that business model innovation is an effective way to funnel the firm’s entrepreneurial orientation into its innovation processes and to increase the success of new product development. Some suggestions for managers and future lines of research are proposed